Global priorities for conservation of reptilian phylogenetic diversity in the face of human impacts - Rikki Gumbs (Nature Portfolio, 2020)
In addition to species richness, evolutionary measures of biodiversity are important considerations for conservation. Here, Gumbs et al. develop new biodiversity metrics incorporating phylogenetic diversity and human pressure and highlight conservation priorities in a global analysis of reptiles.